PENERAPAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARANTEKS EKSPOSISI SISWA SMA - Ayu Wandira; Via Nugraha; Restu Bias Primandhika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is the process of applying the problem based learning model in learning the structure and linguistic rules of exposition text, the effectiveness of the feasibility of the problem based learning model in learning to understand the structure of the exposition text and linguistic rules for students of class X (ten) SMA Bina Nusa Purwajaya in the 2021-2022 academic year. The purpose of this study was to determine the success of the application of the problem based learning model, to describe the process and results of the application of the problem based learning model in exposition text structure learning. This study used descriptive qualitative method. The research instrument used a test and a non-test. Before students take learning to write an exposition text, students must first understand the structure and linguistic rules used in the exposition text. In this study, we will discuss the importance of using problem based learning methods in learning exposition texts in the classroom, because this model will help students and teachers to find solutions for exposition text learning. The results of the research on the application of the problem based learning model after the application of the problem based learning model students obtained 20%. The application of this model is categorized as good.